Some Levels of Plasma Free Fatty Acids and Amino Acids in the Second Trimester Are Linked to Gestational Diabetes and Are Predictive of Persisting Impaired Glucose Tolerance After Delivery - Bartáková, Vendula; Pleskačová, Anna; Pácal, Lukáš; Langmajerová, Monika Skrutková; Smutná, Jindra; Chalásová, Katarína; Eclerová, Veronika; Glatz, Zdeněk; Kaňková, Kateřina; Tomandl, Josef (Journal of clinical medicine, 2025)
Background/Objectives: Gestational diabetes mellitus (GDM) represents an increased metabolic risk in future life for both mother and child. We hypothesize free fatty acids (FFAs) and amino acids (AAs) disturbances in plasma during second trimester might be indicating high risk of persisting glucose intolerance (PGI). The aim of study was to determine plasma FFAs and AAs during pregnancy in women with normal pregnancy and GDM and also in post-GDM women with PGI after delivery and to find potential association of altered FFAs and AAs profile with adverse peripartal outcomes and PGI after GDM. Material and Methods: A total of 54 pregnant women were included in the study. Of those 34 participants had GDM. PGI was diagnosed by oGTT up to one year after delivery. Plasma FFAs were determined using GC-FID and plasma AAs levels were determined using CE-MS method. Results: Decreased levels of tetradecanoic acid and several AAs were found in GDM group during pregnancy. Oleic and docosahexaenoic acid correlated positively while almost all AAs negatively correlated with oGTT values in the pregnancy (all p < 0.05, Spearman). Logistic regression model (using AAs, FFAs and BMI) identified higher citrulline and glutamate levels and lower tetradecenoic acid and choline as the best predictors for postpartum PGI. Some differences in AA levels were detected in women with macrosomic babies. Conclusions: Data support a possible link between GDM development and PGI after delivery and selected metabolite levels. The predictive potential of plasma FFAs and AAs levels on a diabetes risk in future life requires further validation.
Keywords: gestational diabetes mellitus; amino acids; free fatty acids